PENGARUH PENGETAHUAN, PERSEPSI EFEKTIVITAS SISTEM DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK (Studi Kasus Wajib Pajak Orang Pribadi yang Melakukan Kegiatan Usaha yang Terdaftar di KPP Pratama Bangkinang) - Marissa Anggraini; Vince Vince; Susilatri Susilatri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to determine the effect of knowledge, perception of the effectiveness of the tax system and tax penalties on tax compliance, case study on individual taxpayers conducting business listed on KPP Pratama Bangkinang. This study used a primary data was collected by questionnaire distribution to taxpayers. Sample was determined by Slovin formula amounted to 100 taxpayers. Data was collected by using a incidental sampling. The data was analyzed by using the SPSS program to test whether the model used in this study quite appropriate as the model analyzed. Then the regression analysis was used to test the relationship between the variables above. The result of this research indicates that knowledge, perception of the effectiveness of the taxation system and tax penalties each had a positive effect and significant on tax compliance. The effect of independent variables on the dependent variable can only explain by 56,4%. Keywords : knowledge, perception of the effectiveness of the tax system, tax penalties, tax compliance